Understanding flight-test data with CFD rotor simulations: an application case on the H175 helicopter - Leon, E.R.; Desvigne, D.; Embachner, M. (My University, 2022)
In this work, comparisons between flight test data and simulations for the H175 rotor in several flight conditions are proposed. The Computational Fluid Dynamics (CFD) analysis relies on isolated rotor models including different tab arrangements and elastic blades. URANS simulations are performed using the FLOWer solver and are coupled with the comprehensive analysis code CAMRADII, which provides the rotor CSD model and the helicopter trim. A loose-coupling method is applied by exchanging information between the CFD solver and the comprehensive code at each or after several full rotor revolutions until a converged trimmed solution is obtained. The flight test data includes blade control angles, sectional loads, control loads and damper loads allowing for an in-depth comparison between flight and simulations. A full helicopter trim is performed using the comprehensive aeromechanics code HOST in order to extract fuselage attitudes and aerodynamic forces used subsequently as trim targets for the isolated rotor coupled CSD/CFD simulations with 3 degrees of freedom (DoF) trim. Predictive capabilities are thus dependent on accurate modelling of the fuselage drag and download in the initial full helicopter trim, in order to obtain rotor positions and control angles similar to those seen in flight. A conventional (cruise) level flight as well as a high altitude level flight presenting dynamic stall have been simulated and analyzed with a focus on pitch link loads and inter-blade damper loads. Additional cases at higher load factors — namely turn manoeuvers at load factors 1.07g and 1.3g — are also presented.